International Students' Cross-cultural Experiences Of Learning - E. Jones, Michael (Penerbit Universiti Sains Malaysia (USM Press), 2008)
To have an open mind is more important than learning; and we can have an open mind, not by cramming it full of information, but by being aware of our own thoughts and feelings, by carefully observing ourselves and the influences about us, by listening to others, by watching the rich and the poor, the powerful and the lowly. Wisdom does not come through fear and oppression, but through the observation and understanding of everyday incidents in human relationship.